Effect of Aging on the Antifungal Activity and Surface Roughness of Soft Lining Material Incorporated with Chitosan Nano-Particles - Huda Abdul-Wahab Abdul-Shafi; Hawraa Khalid Aziz (Journal of Techniques)
Background: Chitosan is a natural bio-polymer, which has been utilized in different pharmaceutical and biomedical fields, and it has antimicrobial activities. Resilient liner, it’s a polymeric material, considered as a kind of "shock absorber".